Nosebleed or Epistaxis – Homoeopathy Helps (Homoeopathy for All, 2024)
“Epistaxis” is the medical term for   a nosebleed. A nosebleed, meaning   a loss of blood from the tissue   that lines the inside of your nose,   can occur in one or both nostrils.   Usually, it only affects one nostril.  Your nose has many tiny blood   vessels in it. These vessels help   warm and moisten the air you   breathe. But they lie close to the   inner surface of your nose. When air   moves through your nose, it can dry   and irritate your blood vessels. This   makes them very easy to injure or   break, causing a nosebleed.   Although bothersome, most  nosebleeds aren’t serious.  Anyone can get epistaxis. Most  people will have at least one case  in their lifetime. However, some  people are more likely to have a  nosebleed. They include:
Keywords: of nosebleeds; Children; Anterior nosebleed